All in My Head? : The Play of Exclusion and Discrimination in the Labor Market - Das, Maitreyi Bordia (World Bank, Washington, DC, 2015)
Labor market discrimination is very difficult to pinpoint, even more difficult to measure and almost impossible to “prove”. It has been studied in many disciplines of which economics and sociology are prime. The latter has focused more on the manner in which discrimination plays out and how it is related to different forms of social stratification. This paper reviews the literature and makes two main contributions: first, it builds a four-fold typology to think about discrimination—overt or covert; conscious or unconscious; legal or illegal and real or perceived. Second, it identifies screens and filters—devices through which discrimination plays out in the labor market. Unless more empirical studies identify the play of discrimination and exclusion, subordinate groups may well be told that discrimination is actually in their heads—that they are imagining it.